2011
DOI: 10.1074/jbc.m111.286146
|View full text |Cite
|
Sign up to set email alerts
|

A Glycosphingolipid/Caveolin-1 Signaling Complex Inhibits Motility of Human Ovarian Carcinoma Cells

Abstract: Background: Altered cell motility is a crucial aspect determining the invasiveness of tumors. Results: Cells with concomitantly high levels of gangliosides and caveolin-1 have reduced activation of Src and reduced motility. Conclusion: A caveolin-1⅐glycolipid complex can modulate the motility of tumor cells by regulating Src activity Significance: This is a novel mechanism for the control of cell motility by caveolin-1 and gangliosides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Conversely, Src regulated caveolin-1 function through the phosphorylation of caveolin-1 [23]. Recently, Prinetti and coworkers reported that ganglioside GM3/caveolin-1 interactions are potentially important in the motility of ovarian carcinoma cells [24]. Although a correlation between increased ganglioside GM3 levels and increased caveolin-1 expression was reported, the role of GM3 in caveolin-1 oligomerization was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Src regulated caveolin-1 function through the phosphorylation of caveolin-1 [23]. Recently, Prinetti and coworkers reported that ganglioside GM3/caveolin-1 interactions are potentially important in the motility of ovarian carcinoma cells [24]. Although a correlation between increased ganglioside GM3 levels and increased caveolin-1 expression was reported, the role of GM3 in caveolin-1 oligomerization was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, compared to wild-type cells, stable overexpression of sialyltransferase-1 (SAT-1, GM3 synthase) or pharmacological manipulation of A2780 human ovarian cancer cells with N-(4-hydroxyphenyl) retinamide had elevated ganglioside levels, reduced in vitro cell motility, and enhanced expression of the membrane adaptor protein caveolin-1 [26]. In GM3 synthase-overexpressing clones, both depletion of gangliosides by treatment with the glucosylceramide synthase inhibitor D-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol and silencing of caveolin-1 by siRNA increased in vitro cell motility [27]. …”
Section: Discussionmentioning
confidence: 99%
“…TACA expression can be a result of changes in several different steps in the glycoprocessing machinery, including increased/decreased sialylation 1424 or fucosylation 25–29 , increased N-linked glycan branching, altered O-linked glycolipid (ganglioside) compositions 3034 and truncated mucin-type O-glycans. 16,3550 These structures, in part, may modify the physical and chemical properties of the tumor cell, leading to altered cell adhesion and signal transduction, often resulting in enhanced aggressiveness and metastatic potential.…”
Section: Introductionmentioning
confidence: 99%